Aspects of landscape and pollinators-what is important to bee conservation? - Patrício-Roberto, Gleiciani B. [UNESP]; Campos, Maria J.O. [UNESP] (MDPI, 2014)
Pollinators, especially bees, are essential to terrestrial ecosystems. They ensure the maintenance of certain ecological processes, like superior plants' reproduction. In the past decades, agricultural intensification has caused extensive environmental changes, with major impacts on biodiversity, especially on the pollinators, which reflects the loss of fruits and seeds sets. Here, we review studies that elucidate the causes of decline of pollinators, consequences of landscape changes to agriculture and possibilities to bees' conservation. Many studies have related the loss of pollinators to changes in the landscape, such as the conversion of native forests into cultivated areas, which causes loss of important elements for bees (e.g., sources of pollen, nectar and oil, as well as varied nesting sites). Studies involving landscape ecology allow us to assess the effects of different farming practices over the richness and abundance of pollinators. Among the landscape elements performing positive influence on bees, the presence of remaining forests nearby cultivated areas proved to be a very important factor. Nevertheless, studies that evaluate all ground cover with a more integrated approach are still required to assess the effects of landscape context on the diversity and on the abundance of bees related to productivity of crops. Researches like these could provide specific data that strengthen the need for the conservation of different plants and animals, and could offer subsidies to propose necessary information for the execution of public and private policies, aimed at the conservation of the biodiversity. ©2014 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Cropped areas; Fruit and seed sets; Remnant forests; Terrestrial ecosystems